Socialization of uti possidetis juris principles and socio-economic approaches to eliminate separatism in Indonesia - Harefa, Faonaso; Harsono, Cecilia F. (Universitas Islam Malang, 2025)
This study discusses the strategy to overcome the ideology of separatism in Indonesia through the integration of the principle of the Pacidetic Uti juris and the socio-economic approach. The threat of separatism, especially in Papua, remains a serious challenge for national integration. Development inequality, limited economic access, and marginalization narratives become a strong trigger for the growth of disintegration sentiment in the region. The principle of Uti is the posidetic of Juris, which confirms the validity of the boundaries since the decolonization period and provides an international legal basis to strengthen the claims of Indonesia's sovereignty over Papua. On the other hand, sustainable socio-economic policies are believed to be able to reduce the roots of separatism. This study uses mixed methods: qualitative data using NVivo 12 software and quantitative data using interpretive structural modeling (ISM). The results showed that the synergy between inclusive development strategies and the socialization of the principles of Uti Pacidetic Juris as international law could strengthen the sense of nationality and reduce the interest in separatist ideology, especially in Papua. The novelty of this study lies in the integrative approach between juridical and social aspects that have been rarely integrated. The limitations of this study lie in the extent of the scope of the area being analyzed. Further research is advised to explore the implementation of this strategy at the local community level in Papua to test its effectiveness in the long run as part of the national security strategy.